The functions of long non-coding RNAs in colorectal cancer - Wang, Huaiming; Huang, Chengzhi; Yao, Xueqing (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Colorectal cancer (CRC) is the third most prevalent malignant neoplasm worldwide. Recently, in terms of the mechanism of CRC, most studies have focused on protein-coding genes. However, studies have increasingly shown that long non-coding RNAs (lncRNAs) play crucial roles in the proliferation and metastasis of CRC. Investigating this molecular mechanism may provide potential diagnostic tools and therapeutic targets for CRC. This review closely examines the dysregulation of lncRNAs in CRC. On account of different mechanisms being involved in the occurrence and development of CRC, there are several categories of lncRNAs, including lncRNAs related to the Wnt/β-catenin pathway, epithelial mesenchymal transition, epigenetic regulation, angiopoiesis, and chemoresistance. This review summarizes lncRNAs related to the progression of CRC, which may provide insight into the mechanisms and potential markers for prognostic prediction and monitoring relapse of CRC.